Profile of Road Traffic Accident Victims Admitted at Bhayangkara Pusdik Sabhara Porong Hospital - Septyah, Wahyu Estu; Riyanto, Haris Fadillah; Sari, Riska Permata; Aini, Andini Hurul; Fadillah, Abrori (UNUSA Press, 2022)
Background: Traffic accidents are a health problem in forensic medicine that often occurs in society and needs attention, mainly because it is still a major problem in implementing road transportation in Indonesia. Traffic accidents increase yearly along with the increasing number of road users and the ease of ownership of transportation facilities. In 2012, the death toll from traffic accidents in Indonesia was 29,544, with a case fatality rate (CFR) of 14.95%. In 2013, the victims died from traffic accidents, namely 26,416 people, with a case fatality rate (CFR) of 15.98%. In 2014 the victims died due to traffic accidents, namely 28,297 people with a case fatality rate (CFR), traffic accidents of 17.16%. In 2015 the victim died due to traffic accidents, namely 26,185 people with a case fatality rate (CFR) traffic accident of 15.37%. Objective: To describe profile of road traffic accident victims admitted at Bhayangkara Pusdik Sabhara Porong Hospital in 2021-2022. Methods: This research is a retrospective descriptive study. The research sample used was medical record data of traffic accident patients examined at Bhayangkara Pusdik Sabhara Porong Hospital in 2021-2022. Result: The incidence of traffic accidents at Bhayangkara Pusdik Sabhara Porong Hospital can be described as follows; 71.4% are male. Thirteen people (37.1%) are aged 15-29 and based on where the most occurrences on the Surabaya-Malang highway, there are ten people (28.6%), and then based on the time of the incident where the most happened at 12.00 – 18.00, namely 12 people (34.2%), based on the position of the victim where the most were as motorists. Motorcycles have as many as 26 people (74.3%), and based on the type of injury where the most were abrasions is 24 people (40%). Conclusion: The description of the incidence of traffic accidents at the Bhayangkara Pusdik Sabhara Porong Hospital in 2021-2022 is mainly experienced by men of productive age. It occurred on the Surabaya-Malang highway, which has a heavy traffic flow; the time of the incident was during working hours, position the victim was a motorcyclist, and the most common types of injuries were blunt force trauma.